Tinjauan Fiqih Muamalah terhadap Jual Beli Online - Akbar Maulana; Abdul Muttaqin (Moral : Jurnal kajian Pendidikan Islam, 2025)
In the online buying and selling process, the seller becomes the name of the store and the buyer does not know the identity of the seller such as name, address, and even age. Buyers will only know from the name of the store selling the item. The concept of online buying and selling is that you only have information about the name and address of the store, but do not know who the owner of the store is. In the buying and selling process, the buyer chooses the product available in the store and if there are any questions about the product, they can ask the seller via chat. The seller then uses a robotic or human system to answer the buyer's questions. The second pillar and condition is ma'qud 'alaih or a medium of exchange and goods sold. The medium of exchange used in the buying and selling process, both online and offline, still uses the same tool, namely money. The purchase or payment process for online buying and selling can be done through bank transfer through the payment code number that has been ordered. The majority of online stores also offer a wider selection of different types of goods.